Locating learning of toddlers in the individual/society and mind/body divides - Meaney, Tamsin (NOMAD Nordic Studies in Mathematics Education, 2016)
In this paper, theories about learning are discussed in relationship to toddlers locating themselves in space. This is important given the current debate about the mathematics that very young children can or should learn. Regardless of whether learning is seen as an individual or a social activity, learning theories of Piaget and Vygotsky emphasise the cognitive nature of learning and the need for linguistic reflection on that learning. In order not to situate toddlers as deficient or irrational because they do not express their reflections linguistically, I suggest that learning should be considered as problem solving that occurs both with the mind and the body. Using examples of toddlers engaging in spatial explorations, I illustrate how learning mathematics can be reconceptualised in this way.